Problematika Peradilan Koneksitas dalam Menangani Perkara Tindak Pidana Korupsi (Putusan Nomor: 74/Pid.Sus-TPK/2022/PN.Jkt.Pst) - Oktoberiandi, Oktoberiandi; Sujono, Sujono; Sudarto, Sudarto (LITERATUS, 2024)
A connectivity court is a court that functions to try criminal offenses committed jointly by civilians and members of the military (TNI), both general and special crimes, such as corruption. Provisions regarding koneksitas courts are regulated in detail in the Criminal Procedure Code, specifically in CHAPTER XI Article 89 to Article 94, as well as Article 198 to Article 203 in Law Number 31 of 1997 concerning Military Courts. However, in practice, when there is a criminal offense involving members of the TNI and civilians, the case should be resolved through a koneksitas mechanism. In reality, perpetrators are often tried in different courts, with TNI members being tried in military courts and civilian perpetrators in general courts. This creates disparity and ignores the principle of equality before the law, which in turn creates injustice. Law enforcers focus more on procedural justice than on achieving substantial justice.